Rekonstruksi Moral bagi Mahasiswa dalam Pendidikan Islam di Era Society 5.0: Moral Reconstruction for Students in Islamic Education in the Society 5.0 Era - Nabila Intan Permata Sari; Ayu Laila Fitri; Abd. Rachman Assegaf (Educan, 2025)
The moral reconstruction of students in Islamic education is to emphasize the necessity and importance of Islamic education in Indonesia. This arrangement and rearrangement is intended so that Islamic education both institutions and learning materials. In the era of Society 5.0, education integrates seamlessly with technology, enabling students to engage in learning activities alongside advanced technological tools. The disruption brought by technological advancements in education, particularly in Islamic education, is unavoidable. Consequently, educators and stakeholders are increasingly recognizing the critical role of technology in shaping Islamic education within this era. This study adopts a qualitative approach, utilizing a literature review method. Through descriptive analysis, data is collected from written sources, such as books and scientific journals, to explore and describe the reconstruction of Islamic education in the context of Society 5.0.